Learning to BREATHE: Intervensi Berbasis Mindfulness pada Remaja dengan Nonsuicidal Self-Injury (NSSI) (Universitas Muhammadiyah Metro, 2023)
Nonsuicidal Self-Injury (NSSI) is a common condition among adolescents; one of the causes is the inability of individuals to regulate their emotions, resulting in maladaptive coping. Mindfulness-based intervention- is a promising approach to addressing emotional regulation problems in adolescents with NSSI. This case study aims to determine the effect of mindfulness-based intervention, namely Learning to BREATHE (L2B; Broderick & Metz, 2009), in overcoming NSSI in adolescents. The study focused on the case of a 13-year-old girl in 7th grade who underwent a psychological examination for exhibiting risky behaviors (drinking alcohol and smoking), including self-injurious behavior (nonsuicidal). The results of this case study indicate that the L2B program can increase participants' emotion regulation and trait mindfulness and reduce rumination, all related to NSSI conditions. After the intervention, participants gained understanding and various new strategies using a mindfulness approach that can be used to manage emotions and difficult situations until they can be managed and faced more calmly. Participants also feel more sensitive to body sensations and what is happening around them, can spot stressful or intense situations, and know how to react to them.